Filmmaking as Cultural Aggression - Shevchuk, Yuri (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article discusses cinematic depopulation, the strategy of appropriation of the colonized by the colonizer widely used in the Soviet and post-Soviet cinema made in Ukraine and Russia and, until now, never analyzed in academic literature. The cinematic depopulation is a mode of filmic representation whereby a given ethnoscape (Ukraine) is cleansed of its national community (Ukrainians) and instead is populated by the colonizer (Russians) as if it were an integral part of his historical territory. As a form of cultural imperialism, this strategy has, until quite recently, been widely used in both Soviet and post-Soviet Russian and Ukrainian filmmaking to promote the idea of Ukraine conceivable outside of and without the Ukrainian language, culture, and other attributes of Ukrainian identity.